User-driven business model innovation: an ethnographic inquiry into Toutiao in the Chinese context. Issue 3 (27th May 2021) - Chang, Li-Chung; Wang, Xin; Zhang, Su-Qun; Chen, Chang-Bin; Yuan, Zhi-Hong; Zeng, Xian-Ju; Chu, Jian-Qi; Tsai, San-Bing
ABSTRACT: The current firm-driven business model innovation (FDBMI) has found its limits. The aim of this research is to explore the user-driven business model innovation (UDBMI) adopting the ethnographic inquiry approach in the Chinese context. The findings show that UDBMI includes five stages: co-creation of content via interaction, creation release by platform, content spread, effect and flow into cash. It is an inside-out cycle which starts from personal (both fans and creators), then platform, community, and to the whole society lifestyle (culture). In contrast to Chinese culture, western culture is an outside-in cycle which starts from the community, then creators, platform, personal (fans) and finally personal life. This study contributes to advancing the understanding of the UDBMI in the Chinese context, and explains why Toutiao has been able to grow rapidly via value co-creation.